Evaluation of Prognosis of Aortic Valve Stenosis: A New Approach Based on Transvalvular Energy Loss Index - Anguseva, Tanja; Mitrev, Zan; Milojevic, Predrag; Zdravkovska, Milka (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Estimation of aortic valve stenosis is not always sufficient based on standard parameters such as transvalvular pressure gradient (PG) or effective orifice area (EOA). We used transvalvular energy loss index (ELI) to provide more accurate information about myocardial reserve and patient’s prognosis. AIM: The aim of the study was to present the benefit of using ELI as a parameter that provides a more accurate estimation of aortic stenosis (AS) severity and influence on ventricular function. Second objective was to evaluate the performance of this index when predicting the mortality rate of patients. METHODS: In this follow-up trial from 2002 up 2020, we included 377 patients with reconstructive surgery of AS using bovine/equine pericardium, replacing valve cusps on patient’s aortic fibrous ring. Leaflets were implanted separately, using continuous sutures with 2 supported stitches at newly created commissure, without stent or sowing ring. Using transesophageal ultrasound, intraoperatively and postoperatively, we measured EOA, PG, dimensions of aortic annulus, and sinotubular junction of ascending aorta. Applying Bernoulli equation ELI = (EOA×AA)/(AA−EOA), we calculated the values of ELI. RESULTS: The results showed that ELI is influenced by both flow rate and aortic cross-sectional area (AA). Energy loss is systematically higher (15 ± 2%) in large aorta. ELI coefficient accurately predicted energy loss in all situations (r2 = 0.98). ELI was superior to EOA in predicting endpoints, such as early death after surgery. ELI ≤0.42 cm2/m2 strongly correlates with a higher mortality rate. CONCLUSION: ELI has potential to reflect severity of AS better than EOA. It correlates with preserved myocardial reserve. ELI can be used like a parameter for estimating the pre-operative risk of death in patients with moderate/severe AS.